My sister, guard your veil; my brother, guard your eyes uncensored Iranian voices - Azam Zanganeh, Lila (Boston, Massachusetts Beacon Press, 2006)
The brief, often breezy essays, reminiscences, reportage and interviews overturn the facile image of Iran as a single, homogenous entity, providing animated discussions of politics, sex, art, women's rights, and racism, poetic culture, underground nightlife, Tehran's Jewish community, censorship, economic inequality and cross-cultural (mis)understanding under a regime that is highly oppressive but continually subverted.
The stuff that dreams are made of / Azar Nafisi --I grew up thinking I was White / Gelareh Asayesh -- How can one be Persian? / Marjane Satrapi -- From here to mullahcracy / Reza Aslan --Death of a mannequin / Mehrangiz Kar -- The last chapter in the Book of Exodus / Roya Hakakian -- Women without men / a conversation with Shirin Neshat -- Sex in the time of mullahs / Azadeh Moaveni -- Misreading Kundera in Tehran / Naghmeh Zarbafian -- Receding worlds / Daryush Shayegan -- A taste of my cinema /a conversation with Abbas Kiarostami -- An alley greener than the dream of God / Babak Ebrahimian -- Don't cry for me, America / Negar Azimi -- Why acting set me free / a conversation with Shohreh Aghdashloo -- Tehran underground / Salar Abdoh .
Keywords: Women -- Iran -- Social conditions -- 20th century; Women -- Iran -- Social conditions -- 21st century; Iran -- Intellectual life; Iran -- Social conditions